1967
DOI: 10.1111/j.1432-1033.1967.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Sequenator

Abstract: The protein sequenator is an instrument for the automatic determination of amino acid sequences in proteins and peptides. It operates on the principle of the phenylisothiocyanate degradation scheme. The automated process embraces the formation of the phenylthiocarbamyl derivative of the protein and the splitting off of the N-terminal amino acid as thiazolinone. The degradation proceeds a t a rate of 15.4 cycles in 24 hours and with a yield in the individual cycle in excess of 9S0/,. The material requirements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
924
0
20

Year Published

1971
1971
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,852 publications
(951 citation statements)
references
References 15 publications
7
924
0
20
Order By: Relevance
“…On the other hand a single amino acid sequence is determined [ 141 by automated Edman degradation [15] in a Socosi model P 100 sequencer. From the sequence of the first 27 residues, it can be concluded that this neurophysin belongs to the MSEL-neurophysin group [ 141.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand a single amino acid sequence is determined [ 141 by automated Edman degradation [15] in a Socosi model P 100 sequencer. From the sequence of the first 27 residues, it can be concluded that this neurophysin belongs to the MSEL-neurophysin group [ 141.…”
Section: Methodsmentioning
confidence: 99%
“…Arrows indicate the Glu-X bonds of native hirudin cleaved by staphylococcal protease after 1 h digestion (also, see footnote to table 1). Cleavage positions were determined by 4 steps of automatic Edman degradation [25] and percentages of cleavage were based on the recovery of N-terminal Val as 100%. The sequence is taken from [2] and the precise sequence between residues 50-55 has not been established.…”
Section: X17% 31%mentioning
confidence: 99%
“…Manual degradation was by the DABITC-Edman procedure [ 13 ]. The automatic version of the Edman degradation [14] was effected in Beckman 890 C Amino Acid Sequenator. The PTH-amino acids were identified by thin layer chromatography [15] or by HPLC [16].…”
Section: Methodsmentioning
confidence: 99%